Development and Utilization of Introgression Lines Using Synthetic Octaploid Wheat (Aegilops tauschii × Hexaploid Wheat) as Donor - Zhang, Dale; Zhou, Yun; Zhao, Xinpeng; Lv, Linlin; Zhang, Cancan; Li, Junhua; Sun, Guiling; Li, Suoping; Song, Chunpeng (Frontiers in Plant Science, 2018)
As the diploid progenitor of common wheat, Aegilops tauschii Cosson (DD, 2n = 2x = 14) is considered to be a promising genetic resource for the improvement of common wheat. In this work, the efficiency of transferring Ae. tauschii segments to common wheat was clearly improved through the use of synthetic octaploid wheat (AABBDDDD, 2n = 8x = 56) as a “bridge”. The synthetic octaploid was obtained by chromosome doubling of hybrid F1 (Ae. tauschii T015 × common wheat Zhoumai 18). A set of introgression lines (BC1F8) containing 6016 Ae. tauschii segments was developed and displayed significant phenotype variance among lines. Twelve agronomic traits, including growth duration, panicle traits, grain traits, and plant height were evaluated, identifying apparent transgressive segregation in partial lines. Additionally, better agronomic traits could be observed in some lines, compared to the recurrent parent Zhoumai 18. To elucidate the significant variance of those agronomic traits supposedly controlled by Ae. tauschii segments, 14 quantitative trait loci (QTLs) for 3 important agronomic traits (thousand kernel weight, spike length, and plant height) were further located in the two environments (Huixian and Zhongmou), indicating the introgression of favorable alleles from Ae. tauschii into common wheat. This study provides a new strategy to improve common wheat utilizing a single Ae. tauschii genome.